(untitled) (UNED Research Journal, 2022)
Introduction: Fragmentation due to the change in land use because of anthropogenic pressures has caused loss of habitats for many bird species, causing from population mobilizations to local extinctions. Níspero in Cañas, is a coastal community in Costa Rica, which presents a mixed landscape, made up of mangrove patches and tropical dry forest, highly vulnerable due to aquaculture, industrialization, and the increase in the cattle frontier. One of the proposed strategies for the conservation of these ecosystems is the sustainable use of natural resources. However, there is still profound lack of knowledge about the bird communities present in these heterogeneous ecological matrices Objective: to characterize the diversity of birdlife in a fragmented landscape. Methods: From July 2018 to January 2019, bird counts were carried out. The sampling sites were classified into four categories: mangrove, pasture, shrimp farms and deciduous forest. General alpha richness, abundance, and diversity were determined for each site. Results: A total 1109 individuals distributed in 42 families, 97 genera and 125 species were registered. The most representative families were Ardeidae and Tyrannidae. Shrimp farms had the highest richness indexes, followed by mangrove and pasture areas. In terms of diversity, no significant differences were found. Conclusion: This first approach demonstrates the importance of efforts to integrate disturbed landscapes into conservation programs, given that they present new ecological configurations that can be exploited by various bird species.